MAKNA SIMBOLIK SENI PERTUNJUKAN BARONGSAI DALAM KEBUDAYAAN TIONGHOA DI KOTA PEKANBARU - Ridn "; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The performances art of lion dance is one of the values unique cultural heritage thatpresent and grow in Pekanbaru city. In the performances art of lion dance, there are symbolicaspects that is rich in mean and represented by phsical objects, musical intstruments, clothingand lion dance movements. So, the purpose of this researh was determining the meaning ofsymbolic situation, for determining the product of social interaction, and for determining theinterpretation of the performances art of lion dance in Tionghoa Cultural in Pekanbaru city.This research used qualitative methode by symbolic interaction approach. The subject ofresearch are four HBT (Himpunan Bersatu Teguh)’s lion dance players and four HTT(Himpunan Tjinta Teman)’s lion dance players as key informants and informan were selectedby using purposive technique. As supporting informant, one figure of Tionghoa community wasselected by purposive technique and three lion dance’s audiences were selected by accidentaltechnique. Data collection technique used participant observation, in-depth interview, anddocumentation.The result of research showed that symbolic situation in the performances art of liondance in Pekanbaru city include physical objects such as the main instrument (the head of sai),musical intstruments (drums, cymbals and gongs), and lion dance’s costumes which adoptedfrom the color of the character of Sam Kok Legend. While the social objects from theperformances art of lion dance include the movements of lion dances’s players. The product ofsocial interaction includes meaning of the performences art of lion dance is the meaning fromthe players’ side, lion dance is meant as a culture value and sport; lion dance is meant byTionghoa’s figure as solidarity value, culture, spiritual, and art; while lion dance is meant byaudiences as art value and spiritual. Interpretation the performances art of lion dance includethe closed action and the opened action. The closed action include internal motivation of liondance’s players (passion and get achievement), external motivation (encouragement of familyand friends), and both of pleasure and proud become lion dances’s players because able to getthe achievment in lion dance’s competitions. The opened action of lion dance’s players includethe face expression of instrumentals’ players who focus on the rhythm of the game and theattitude of lion dance’s players who were cooperative in teamwork, solid, discipline andconsistent in following the practice for implementation of the performances art of lion dance.Keywords : Symbolic Meaning, Lion Dance, Symbolic Situation, The product of SocialInteraction, Interpretation